CVD synthesis of graphene nanoplates on MgO support - Jugade, Ravin M.; Sharma, Shalini; Gokhale, Suresh (Materials Science-Poland, 2014)
Synthesis of graphene directly on MgO has been carried out and the structural properties of the obtained material have been investigated. Few-layered graphene was produced by simple thermal decomposition of methane over MgO powder at 950 A degrees C in a CVD reactor. The samples were purified by 10 N HNO3 treatment, and studied by TEM, Raman spectroscopy, EDAX and SEM. TEM clearly indicated the formation of graphene. EDAX showed that the purified sample contained only carbon and no traces of MgO. The characteristic Raman features of graphene were also seen as D-band at 1316 cm(-1), G-band at 1602 cm(-1), and a small 2D-band at 2700 cm(-1) in the Raman spectra. The strong D-band suggests that the graphene possess large number of boundary defects. The small 2D-band indicates the formation of few-layered graphene.
Keywords: graphene; magnesium oxide; nanographene